Enhancing autophagy and energy metabolism in the meniscus can delay the occurrence of PTOA in ACLT rat - Zhu, Huangrong; Liu, Hai; Chen, Xizhong; Xu, Xin; Zhang, Shuqin; Xie, Denghui (Frontiers in Cell and Developmental Biology, 2022)
Osteoarthritis (OA) is a progressive degenerative joint disease characterized by the destruction of the articular cartilage, meniscus and the like. Autophagy and cellular energy metabolism are the mechanisms by which cells maintain homeostasis. However, little is known about the effects of autophagy and cellular energy metabolism on meniscus degeneration, and the pathogenesis of posttraumatic osteoarthritis (PTOA) after the meniscal injury is rarely reported. Therefore, this study aimed to investigate the relationship between changes in autophagy and cellular energy metabolism in the meniscus following anterior cruciate ligament transection (ACLT) and PTOA induced by subsequent articular cartilage injury. In this study, we use a combination of cell experiments in vitro and animal experiments in vivo. On the one hand, cell experiment results show that inhibiting the mTORC1 signaling pathway by inhibiting the phosphorylation of S6K and AKT proteins in meniscal cells will lead to the increase of Beclin1, LC-3B, ATG12, ULK1, P62, and activate autophagy-related signaling pathways, which in turn protects the extracellular matrix component COL1 of meniscal cells from degradation by catabolic factor MMP13. In addition, it increased the generation of mitochondrial membrane potential in meniscal cells, increased the expression of anti-apoptotic factor BCL-XL, decreased the expression of pro-apoptotic factors BAD and BAX, and reduced the apoptosis of meniscal cells. More importantly, under the stimulation of inflammatory factor IL-1β, the secretion of meniscus cells can reduce the elevated levels of MMP13 and Adamts5 caused by chondrocytes affected by IL-1β. On the other hand, the results of animal experiments in vivo further proved the validity of the results of the cell experiments, and also proved that the meniscus injury did prior to the articular cartilage degeneration after ACLT. In conclusion, this study suggests that the meniscus prior to articular cartilage damage during the development of PTOA after ACLT, and that promoting autophagy and energy metabolism of meniscal cells may be a potential therapeutic target for delaying PTOA.